2011
DOI: 10.1155/2011/352819
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Flow Loss Reduction in a Turbine Cascade with a Linearly Varied Height Streamwise Endwall Fence

Abstract: The present study attempts to reduce secondary flow losses by application of streamwise endwall fence. After comprehensive analysis on selection of objective function for secondary flow loss reduction, coefficient of secondary kinetic energy (CSKE) is selected as the objective function in this study. A fence whose height varies linearly from the leading edge to the trailing edge and located in the middle of the flow passage produces least CSKE and is the optimum fence. The reduction in CSKE by the optimum fenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the present work, the turbulence model utilized in all the cases is one of the variants of the well-known turbulence model available within CFDRC, known as the shear stress transport (SST) model, which employ averaged governing equations to solve for the mean flow quantities and provide the distribution of the turbulent viscosity that is needed in the approximations of the Equation (2). The predictions utilizing this model were validated and compared with the experimental data by many researchers [40][41][42] and found that the SST model provided the most appropriate prediction of behavior of similar cases such as film cooling. The SST model is a two equation model presented by Menter.…”
Section: Turbulence Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, the turbulence model utilized in all the cases is one of the variants of the well-known turbulence model available within CFDRC, known as the shear stress transport (SST) model, which employ averaged governing equations to solve for the mean flow quantities and provide the distribution of the turbulent viscosity that is needed in the approximations of the Equation (2). The predictions utilizing this model were validated and compared with the experimental data by many researchers [40][41][42] and found that the SST model provided the most appropriate prediction of behavior of similar cases such as film cooling. The SST model is a two equation model presented by Menter.…”
Section: Turbulence Modelmentioning
confidence: 99%
“…This model utilizes a blending function that allows switching between the k-model in the sub and log layer and the -model in the outer region of the boundary layer and in free-shear flows. 35 The complete formulation of the SST model is given as follows 40 :…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Endwall fence technique has been utilized to reduce secondary flow loss in turbine cascades for a long history. Experimental investigations of (Kawai 1994) and Govardhan and Kumar (2011) found that fence with 1/3 height of the inlet boundary layer thickness when located half a pitch away from the blade suction side is optimal. Moreover, (Moon and Koh 2001) have simulated the complicated vortex structure of flow field in turbine cascade with and without endwall fence, which leads to an understanding on the formation of counter-rotating streamwise fence vortex and explains the mechanism of controlling secondary flow development.…”
Section: Introductionmentioning
confidence: 99%
“…Moser et al [8] designed an optimized radially profiled axisymmetric casing for a guide vane of a steam turbine stage that reduced the stage loss over a wide range of pressure ratios. Kumar and Govardhan [9] applied a streamwise end wall fence to reduce secondary flow losses in a linear turbine cascade. They predicted reductions in the exit flow angle deviation, secondary flow losses, and the magnitude and spanwise penetration of the passage vortex.…”
Section: Introductionmentioning
confidence: 99%